Panel Data Approach Evaluation of Outsourcing and Inventory Holding Preventive Maintenance Costs for Industrial Vessel's Operations in Nigeria - Charles Ochiabuto Anyadiegwu; Theophilus Chinoyerem Nwokedi; Obed C. Ndikom; Donatus E. Onwuegbuchunam; Nnaemeka Charles Ezeanya (Journal of Eta Maritime Science, 2025)
This study investigated the cost implications of maintenance outsourcing (MO) and inventory management (IM) strategies as preventive maintenance measures for industrial vessel operations in Nigeria. Secondary data were gathered through a survey of five major offshore service vessel operators, comprising three anchor handling tug supply (AHTS) operators and two security escort vessel operators The dataset covered 15 years, from 2006 to 2020, detailing fleet size, MO costs, inventory holding costs, and the breakdown rates of vessels. The findings, derived from a panel data regression model and rate of change analysis, indicate that MO and inventory holding costs are significant drivers of breakdown and repair expenditures in both AHTS and security escort vessels. Average fleet-size-to-cost ratios stand at around 1: 67,589,220; 1: 8,380,329; and 1: 14,613,931 for per-vessel breakdown repair costs, outsourcing expenditure, and inventory holding costs, respectively. Outsourcing of maintenance accounts for 12.4% while inventory holding accounts for 21.6% of the total cost of maintenance per vessel, respectively, playing an important role in reducing operational stoppages. These results indicate that the optimization of outsourcing and IM expenditure assumes strategic relevance in improving the preventive maintenance practices in Nigeria's offshore sector. This pursuit aims for more sustainable and efficient operations for its industrial vessels.